Electroreduction of CO2 by Hybrid Cu-TiO2/rGO Catalyst: Qualitative Detection of Products using Rotating Ring Disc Electrode - Koyejo, Adefunke O.; Chu, Xia; Kesavan, Lokesh; Damlin, Pia; Kvarnström, Carita (WILEY-V C H VERLAG GMBH, 2025)
The electrochemical reduction of CO2 (ERCO2) to valuable chemicals such as acetic acid/acetate offers a promising route to revolutionize chemical production and enhance sustainability. Here, we report the hydrothermal preparation of an electrocatalyst consisting of copper/titanium dioxide/reduced graphene oxide (Cu-TiO2/rGO) for ERCO2 in aqueous medium. The metal-support (TiO2/rGO) was pre-synthesized by combining an aqueous solution of TiO2 and GO in an autoclave at 150 degrees C for 20 h. Then TiO2/rGO was added to synthesized Cu colloid formed through the reduction of copper (II) nitrate trihydrate resulting in the formation of Cu-TiO2/rGO. The Cu-TiO2/rGO hybrid nanocomposite was fully characterized using spectroscopic and microscopic techniques. This study explored the versatility of the rotating ring-disc electrode (RRDE) as an in situ electroanalytical tool for the selective detection of products formed during ERCO2. The well-designed hybrid electrocatalyst, containing Cu-0/Cu+ active sites, facilitated the eight-electron transfer for acetic acid (AA) formation at low potentials. AA formation was detected on the RRDE and validated by conventional NMR and HPLC techniques. This work highlights and expands the scope of selective hydrogenation of CO2 towards value-added products.